A behavioural and ERP investigation of the wearable camera photo review in autobiographical memory. Issue 2 (7th February 2021) - Khachatoorian, N.; Loveday, C.; Dima, D.; Mair, A.; Illingworth, S.; Conway, M. A.; Haenschel, C.
ABSTRACT: Wearable camera photo review has successfully been used to enhance memory, yet very little is known about the underlying mechanisms. Here, the sequential presentation of wearable camera photos – a key feature of wearable camera photo review – is examined using behavioural and EEG measures. Twelve female participants were taken on a walking tour, stopping at a series of predefined targets, while wearing a camera that captured photographs automatically. A sequence of four photos leading to these targets was selected (∼ 200 trials) and together with control photos, these were used in a recognition task one week later. Participants' recognition performance improved with the sequence of photos (measured in hit rates, correct rejections, & sensitivity), revealing for the first time, a positive effect of sequence of photos in wearable camera photo review. This has important implications for understanding the sequential and cumulative effects of cues on episodic remembering. An old-new ERP effect was also observed over visual regions for hits vs. correct rejections, highlighting the importance of visual processing not only for perception but also for the location of activated memory representations.